Epidemiology and economic burden of meningococcal disease in Germany: A systematic review. Issue 13 (18th March 2022) - Gruhn, S.; Witte, J.; Greiner, W.; Damm, O.; Dietzsch, M.; Kramer, R.; Knuf, M.
Highlights: Annual IMD incidence in Germany was at 0.3 cases per 100, 000 persons in 2019. IMD incidence has gradually decreased, mainly attributable to less MenB cases. Cases with MenY and MenW have increased especially in young adults in recent years. High direct and indirect costs illustrate the public health relevance of IMD. Data on long-term economic burden and indirect costs are lacking. Abstract: Introduction: Invasive meningococcal disease (IMD) is a notifiable disease in Germany and other European countries. Due to the high lethality of the disease and the risk of long-term consequences, IMD prevention is of high public health relevance despite the low number of cases in the population. This study aims to describe key epidemiological and economic parameters of IMD in Germany to support national decision-making processes for implementing enhanced prevention measures. Methods: Based on a systematic literature review in PubMed and EMBASE, all publications on the burden of disease and costs of IMD published up to May 2020 were evaluated. Additionally, notification data were used to report the annual case numbers and incidence of IMD in Germany until the end of 2019. Results: Thirty-six studies were included, of which 35 reported data on the epidemiological burden of disease and three reported data on economic aspects of IMD. The type of reported endpoints and results on the incidence of IMD differed widely by reporting year, population, and data source used. Most of the data are reported without specific information about a serogroup. Data on the economic burden of disease and healthcare resource use are scarce. Based on mandatory notification data, a decrease in the incidence of notified IMD cases has been observed since 2004. Currently, the nationwide annual incidence in Germany is at 0.3 cases per 100, 000 persons and has gradually decreased. While the overall decline is mainly attributable to MenB, cases with MenY and MenW are the only ones that have increased on a low level in recent years. Conclusion: While IMD is a rare disease, high direct and indirect costs illustrate the relevance of the disease for patients, caregivers, as well as for the health care system. Future research should concentrate on quantifying the long-term economic burden and indirect costs of meningococcal disease. Integrated IMD surveillance with isolate characterisation remains crucial to inform public health policies.